Implementation of Unwritten Law as a Breakthrough in Criminal Law Enforcement in Indonesia - Faisal Arif; Bernat Panjaitan; Nimrot Siahaan (International Journal Labs, 2023)
Based on the constitution, the State of Indonesia is a state of law not based on a single absolute power. Thus, the Indonesian government has limited powers and is not allowed to take actions outside the applicable legal norms. This means that in Indonesian constitutional practice, the law should rule power and not vice versa. However, in reality, the condition of law enforcement in Indonesia is very poor and far from expectations. There is discrimination against justice seekers where ordinary people with all limited resources always lose to the buttocks who own capital and can buy and play with the law at will. As a result, a sharp sword term appears below, but blunt upwards. To overcome these problems, it is necessary to develop the role of the prosecutor's office to also apply unwritten laws not only written to various forms of criminal cases. Thus, the needs of the community from the aspects of welfare and justice can be realized.